Efficacy and Safety of Anti-PD1/PDL1 in Advanced Biliary Tract Cancer: A Systematic Review and Meta-Analysis - Jiang, Qi; Huang, Jinsheng; Zhang, Bei; Li, Xujia; Chen, Xiuxing; Cui, Bokang; Li, Shengping; Guo, Guifang (Frontiers in Immunology, 2022)
Background: Anti-programmed cell death protein 1 and its ligand (anti-PD1/PDL1) has been proposed as a promising therapeutic option for advanced biliary tract cancer (aBTC). Given the scarce quantitative analyses of anti-PD1/PDL1 in aBTC, we thus did a meta-analysis to assess the benefits and risks of this emerging treatment strategy in patients with aBTC. Methods: PubMed, Embase, the Cochrane Library and Web of Science were searched for relevant studies. The main endpoints were median progression-free survival (mPFS), median overall survival (mOS), objective response rate (ORR), disease control rate (DCR), any-grade adverse events (AEs) and grade 3-4 AEs. Results: Twenty-eight studies with 1338 participants were included. The mPFS, mOS, ORR and DCR were 2.5 months, 7.6 months, 6.8% and 34.7% in anti-PD1/PDL1 monotherapy group, 4.9 months, 10.2 months, 17.5% and 68.7% in anti-PD1/PDL1 plus antiangiogenesis group, 2.9 months, 8.3 months, 9.9% and 36.8% in anti-PD1/PDL1 plus anti-cytotoxic T lymphocyte antigen 4 (anti-CTLA4) group, 8.2 months, 14.8 months, 36.3% and 84.6% in anti-PD1/PDL1 plus chemotherapy group, and 12.4 months, 16.0 months, 45.1% and 95.0% in anti-PD1/PDL1 combined with anti-CTLA4 and chemotherapy group, respectively. Compared with anti-PD1-containing regimens, anti-PDL1-containing regimens achieved preferable mPFS (11.1 vs. 3.8 months), mOS (12.2 vs. 9.8 months) and ORR (23.7% vs. 17.4%), despite a similar DCR (61.1% vs. 61.3%). The mPFS, mOS, ORR and DCR of first-line anti-PD1/PDL1 were 10.6 months, 15.8 months, 42.3% and 88.6%, and of second-line therapy or beyond were 3.0 months, 9.1 months, 11.6% and 51.1%, respectively. There were 80.6% and 34.0% of the patients suffering any-grade AEs and grade 3-4 AEs. Conclusions: Anti-PD1/PDL1 showed encouraging efficacy and acceptable safety profile in aBTC, and thus could be an alternative treatment.